2019
DOI: 10.1055/s-0039-1688820
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-Day Mortality in Neonatal Gram-Negative Bacilli Sepsis

Abstract: Objective Multidrug-resistant gram-negative bacilli (MDR-GNB) have emerged globally as a serious threat and with a high case fatality rate (CFR). Study Design We performed a case–control study in a Thai neonatal intensive care unit to identify the risk factors for 30-day CFR of GNB sepsis between 1991 and 2017. The CFR was analyzed by Cox's proportional hazards model. Results For 27 years, the percentage of MDR-GNB from GNB sepsis was 66% (169/257). The medians (interquartile ranges) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(35 reference statements)
1
9
1
Order By: Relevance
“…The time to recovery of NS in neonates with septic shock were delayed by 92% as compared to neonates without septic shock. Similar associations have been found in previously conducted study of Thailand and the systematic review of prognosis [40,50]. Septic shock was independently associated with bacteremia-related neurologic complications or sequelae [46].…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…The time to recovery of NS in neonates with septic shock were delayed by 92% as compared to neonates without septic shock. Similar associations have been found in previously conducted study of Thailand and the systematic review of prognosis [40,50]. Septic shock was independently associated with bacteremia-related neurologic complications or sequelae [46].…”
Section: Plos Onesupporting
confidence: 88%
“…Previous studies and reviews have shown that risk factors that significantly affect the survival status of neonates with sepsis are prematurity, Low Birth Weight (LBW), low APGAR score, a requirement of assisted ventilation, intrapartum fever, chorioamnionitis, the induced onset of labor, young age at admission, organ dysfunction, infectious complications, poor feeding, prolonged Capillary Refilling Time (CRT), cyanosis, convulsions, septic shock, lethargy, nasogastric tube feeding, LONS, sex of neonate, and unable to initiate early Exclusive Breastfeeding (EBF) [13,14,16,24,[27][28][29][30][31][32][33][34][35][36][37][38]. Furthermore, it is mainly affected by the type of bacterial isolates in the blood culture [3,26,36,[39][40][41]. In addition, delays in the identification, initiation of treatment, care-seeking at the household level, and the lack of access to high-quality services contribute to the poor recovery rate of NS [6,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Some large cohorts have not found a clear correlation between AMR and adverse outcome [8,12,13]. Data from this small study did not confirm a significant impact of resistance profile on neonatal mortality [5].…”
Section: Discussioncontrasting
confidence: 71%
“…Appropriate empirical treatment is considered crucially important in reducing mortality. However, despite the improvement in neonatal care, the 2 of 17 fatality rate in babies with GN-BSIs remains around 15-20%, also during the emergence of antimicrobial resistance (AMR) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in developed countries, the incidence is lower, with estimates around 0.2-0.3 per 1,000 live births, an overall mortality rate of 10% with 50% of cases having some form of disability at 5-year follow-up is observed [4,8,11]. Neonatal multidrug-resistant (MDR) sepsis and meningitis are a serious threat because of their high mortality and morbidity [8,10,12,13]. Incidence of multidrug-resistant (MDR) meningitis was 41%, and increased from 32% (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) to 58% (2003-2014); however, there was no statistically significant difference [10].…”
Section: Introductionmentioning
confidence: 99%